Macrophage efferocytosis in atherosclerosis. (10th January 2023) - Baraniecki, Łukasz; Tokarz‐Deptuła, Beata; Syrenicz, Anhelli; Deptuła, Wiesław
Abstract: This paper presents the role of macrophage efferocytosis, the process of elimination of apoptotic bodies—elements formed during vascular atherosclerosis. The mechanisms of macrophage efferocytosis are presented, introducing the specific signals of this process, that is, 'find me', 'eat me' and 'don't eat me'. The role of the process of efferocytosis in the formation of vascular atherosclerosis is also presented, including the factors and mechanisms that determine it, as well as the factors that determine the maintenance of homeostasis in the vessels, including the formation of vascular atherosclerosis.